Non-typeable Haemophilus influenzae–Moraxella catarrhalis vaccine for the prevention of exacerbations in chronic obstructive pulmonary disease: a multicentre, randomised, placebo-controlled, observer-blinded, proof-of-concept, phase 2b trial. Issue 5 (May 2022) - Andreas, Stefan; Testa, Marco; Boyer, Laurent; Brusselle, Guy; Janssens, Wim; Kerwin, Edward; Papi, Alberto; Pek, Bonavuth; Puente-Maestu, Luis; Saralaya, Dinesh; Watz, Henrik; Wilkinson, Tom M A; et al.
Summary: Background: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are associated with changes in the sputum microbiome, including an increased prevalence of pathogenic bacteria. Vaccination against the most frequent bacteria identified in AECOPD might reduce exacerbation frequency. We assessed the efficacy, safety, and immunogenicity of a candidate vaccine containing surface proteins from non-typeable Haemophilus influenzae (NTHi) and Moraxella catarrhalis (Mcat) in patients with COPD. Methods: This multicentre, randomised, observer-blinded, placebo-controlled, proof-of-concept, phase 2b trial recruited patients with stable COPD, moderate-to-very severe airflow limitation (Global Initiative for Chronic Obstructive Lung Disease [GOLD] stage 2, 3, or 4), at 67 clinical sites in Belgium, Canada, France, Germany, Italy, Spain, UK, and USA. Eligible patients were aged 40–80 years and had a history of at least one moderate or severe exacerbation in the previous year. Patients were allocated (1:1) using a minimisation algorithm to receive two intramuscular injections of NTHi–Mcat vaccine or placebo 60 days apart, in addition to standard care. The allocation algorithm considered age category, number of previous exacerbations, COPD severity at study entry, and country as minimisation factors, to guarantee treatment balance within each factor. Vaccine recipients and those responsible for evaluating study endpoints were masked to group allocation. In the analysis of efficacy, the primary outcome was the rate of any moderate or severe AECOPD occurring within a 1-year period, starting 1 month after the second dose in patients who received two vaccine doses (modified total vaccinated cohort). Safety was assessed in the total vaccinated cohort. The trial is registered with ClinicalTrials.gov, number NCT03281876, and is complete. Findings: Between Nov 27, 2017, and Nov 30, 2018, 606 adults were enrolled and included in the total vaccinated cohort (304 in the NTHi–Mcat vaccine group, 302 in the placebo group); 571 received two doses and were included in the primary efficacy analysis (279 in the NTHi–Mcat vaccine group, 292 in the placebo group). 23 participants dropped-out in the NTHi–Mcat vaccine group and 39 in the placebo group; this included 4 patients in the NTHi–Mcat vaccine group and 15 in the placebo group who withdrew from the study because of an adverse event. The primary analysis included 340 exacerbations (in follow-up time 102 123 days) in the NTHi–Mcat vaccine group and 333 (in 104 443 days) in the placebo group, with a yearly rate of moderate or severe AECOPD of 1·22 in the NTHi–Mcat vaccine group and 1·17 in the placebo group, with vaccine efficacy in reducing the yearly rate of moderate or severe AECOPD estimated to be zero (vaccine efficacy point estimate 2·26% [87% CI –18·27 to 11·58]; p=0·82). Solicited local adverse events were more frequent in the NTHi–Mcat vaccine group (216 [72%] of 301 patients) than with placebo (34 [11%] of 299 patients), and the frequency of solicited general adverse events was similar between groups (239 [79%] of 301 vs 235 [79%] of 299 patients). There was one death in the NTHi–Mcat vaccine group (acute respiratory failure, not related to vaccination) and ten in the placebo group (seven due in part to COPD or respiratory failure). There were 158 serious adverse events (89 [29%] of 304 patients) in the NTHi–Mcat vaccine group, not related to vaccination, and 214 (99 [33%] of 302 patients) in the placebo group. Interpretation: NTHi–Mcat vaccine administered to patients with COPD did not show efficacy in reducing the yearly rate of moderate or severe exacerbations. No safety concerns were identified. Funding: GlaxoSmithKline Biologicals SA.